Hypoxia Promotes Gastric Cancer Malignancy Partly through the HIF-1α Dependent Transcriptional Activation of the Long Non-coding RNA GAPLINC - Liu, Lei; Zhao, Xihe; Zou, Huawei; Bai, Rubing; Yang, Keyu; Tian, Zhong (Frontiers in Physiology, 2016)
Hypoxia-inducible factor (HIF) activates the transcription of genes involved in cancer progression. Recently, HIF was reported to regulate the transcription of non-coding RNAs. Here, we show that the transcription of a long non-coding RNA (lncRNA), Gastric Adenocarcinoma Associated, Positive CD44 Regulator, Long Intergenic Non-Coding RNA (GAPLINC), is directly activated by HIF-1α in gastric cancer (GC). GAPLINC was overexpressed in GC tissues and promoted tumor migration and invasive behavior. GAPLINC overexpression was associated with poor prognosis in GC patients. Luciferase reporter assays and chromatin immunoprecipitation assays confirmed that HIF-1α binds to the promoter region of GAPLINC and activates its transcription. GAPLINC knockdown inhibited hypoxia-induced tumor proliferation in vivo. Taken together, our results identified a novel role for HIF transcriptional pathways in GC tumorigenesis mediated by the regulation of the lncRNA GAPLINC, and suggest GAPLINC as a novel therapeutic target for reversing chemoradioresistance and prolonging survival.